How important is aerial leaf litter for insectivorous birds foraging in a Malaysian tropical forest? - Mansor, Mohammad Saiful; Rozali, Fasihah Zarifah; Abdullah, Nurul Ashikin; Nor, Shukor Md; Ramli, Rosli (Elsevier, 2019)
Aerial leaf litter is a vital resource for insectivorous birds in tropical forests, particularly those that rely on dietary litter-dependent arthropods. The present study quantified and determined aerial-leaf litter selection patterns of specialist and regular dead-leaf users. In total, 486 observation sessions were conducted in a lowland tropical forest from February 2014 to September 2015. At least two ‘specialist’ species (over 75% of the observations) and seven ‘regular users’ species (25–74% of the observations) were found foraging for arthropods among aerial curled dead leaves within the aboveground vertical vegetation layers. These species belonged to four genera of the family Timaliidae and Pellorneidae: Cyanoderma, Stachyris, Pellorneum, and Malacopteron. The chestnut-winged babbler (Cyanoderma erythropterum) and the black-throated babbler (Stachyris nigricollis) were two species that heavily exploited the aerial leaf litter, accounting for 89% and 76% of the observations, respectively. The present study indicates that aerial leaf litter could serve as a vital foraging resource for most gleaning forest babblers in Malaysian rainforests. Moreover, niche separation among these dead-leaf foragers occurred due to their differing vertical strata preferences. The variations in body and bill sizes among the studied species suggest that they consume various arthropod sizes and taxonomic groups. A morphological analysis identified Hymenoptera, Coleoptera, and Arachnida as the dominant litter-dependent arthropods, and a molecular analysis revealed the presence of additional insect groups in the aerial leaf litter (e.g. Diptera and Lepidoptera). This study highlights the importance of maintaining undergrowth vegetation that can intercept aerial leaf litter to provide important foraging opportunities for forest bird species. © 2019